Horizontal Inequity in Healthcare Delivery: A Qualitative Analysis of Perceptions of Locality and Costs of Access in the Jirapa Municipality, North‐western Ghana. (18th July 2020) - Domapielle, Maximillian Kolbe; Akurugu, Constance Awinpoka; Mdee, Anna
Abstract: This article provides evidence of horizontal inequity in the distribution of the burden and benefits of healthcare in north‐western Ghana. A qualitative approach was used to collect and analyse the data on variation in perceptions of affordability of health services to rural and urban populations in the Jirapa Municipality of Ghana. The article argues that costs of transportation, food and lodging associated with seeking healthcare at the municipal referral hospital are disproportionately higher for rural residents. This leads to delayed medical treatment, self‐medication or reliance on traditional medicines, all of which can come with harmful consequences. © 2020 John Wiley & Sons, Ltd.